1978
DOI: 10.1159/000237803
|View full text |Cite
|
Sign up to set email alerts
|

Streptomycin Pharmacokinetics in Malnutrition

Abstract: Pharmacokinetic parameters of streptomycin such as plasma concentration, plasma half-life, urinary excretion, and in vitro and in vivo binding to plasma proteins were studied in undernourished and well-nourished individuals. None of the parameters studied were different in undernourished subjects as compared to those in well-nourished, in spite of significant differences in mean albumin values between the two groups. This may be attributed to unaltered protein binding of the drug in undernourished subjects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Protein deficiency, lipids, micronutrients, and vitamins can all affect hepatic microsomal drug metabolism 24 , 25 . These studies provide some support to the suggestion that the nutritional status of an elderly patient may well cause changes in the pharmacokinetic parameters of several drugs 26–39 . It is reasonable to speculate that if pharmacokinetics are affected by malnutrition, the elderly would be most at risk.…”
Section: Pharmacokinetics and The Elderlysupporting
confidence: 56%
“…Protein deficiency, lipids, micronutrients, and vitamins can all affect hepatic microsomal drug metabolism 24 , 25 . These studies provide some support to the suggestion that the nutritional status of an elderly patient may well cause changes in the pharmacokinetic parameters of several drugs 26–39 . It is reasonable to speculate that if pharmacokinetics are affected by malnutrition, the elderly would be most at risk.…”
Section: Pharmacokinetics and The Elderlysupporting
confidence: 56%
“…In undernourished patients, in vitro binding is 61.9 ± 3.87% and in vivo 47.3 ± 6.86%. Only 50% of the protein bound streptomycin is accounted for by binding to albumin; the rest is bound to globulins (Prasad and Krishnaswamy, 1978). Other recent studies have indicated in vitro binding of 35% in normal serum and 19% in patients with kwashiorkor (Buchanan, 1977;Buchanan and van der Walt, 1977).…”
Section: Streptomycinmentioning
confidence: 98%
“…Concentrations of 10 j.lgjml are considered adequate for treatment; however, levels as low as 0.4 ILgjml may inhibit growth of M. tuberculosis (Bobrowitz, 1970(Bobrowitz, , 1974Prasad and Krishnaswamy, 1978). Earlier reports indicate that intravenous, intramuscular or subcutaneous injections yield approximately the same serum concentrations within 2 hours (Adcock and Hettig, 1946;Anderson and Jewell, 1945;Buggs et aI., 1946).…”
Section: Streptomycinmentioning
confidence: 99%
See 2 more Smart Citations